2018
DOI: 10.1371/journal.pone.0195165
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 3 (TLR3) promotes the resolution of Chlamydia muridarum genital tract infection in congenic C57BL/6N mice

Abstract: Chlamydia trachomatis urogenital serovars primarily replicate in epithelial cells lining the reproductive tract. Epithelial cells recognize Chlamydia through cell surface and cytosolic receptors, and/or endosomal innate receptors such as Toll-like receptors (TLRs). Activation of these receptors triggers both innate and adaptive immune mechanisms that are required for chlamydial clearance, but are also responsible for the immunopathology in the reproductive tract. We previously demonstrated that Chlamydia murid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(56 citation statements)
references
References 79 publications
(122 reference statements)
13
40
0
Order By: Relevance
“…Our research focuses on the impact of TLR3 signaling on the immune response to chlamydial infection in oviduct epithelium, and we were the first to demonstrate more severe genital tract pathogenesis in mice deficient in TLR3 confirming our hypothesis that TLR3 has a protective role in the immune responses to murine genital tract infections (32). In this investigation, our goal was to ascertain whether TLR3 had a similar protective role in the immune response to genital tract Chlamydia infection in humans and to more precisely delineate those immune responses in oviduct epithelial cells that contribute to the fibrosis and scarring that lead to reproductive sequelae in clinical disease.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Our research focuses on the impact of TLR3 signaling on the immune response to chlamydial infection in oviduct epithelium, and we were the first to demonstrate more severe genital tract pathogenesis in mice deficient in TLR3 confirming our hypothesis that TLR3 has a protective role in the immune responses to murine genital tract infections (32). In this investigation, our goal was to ascertain whether TLR3 had a similar protective role in the immune response to genital tract Chlamydia infection in humans and to more precisely delineate those immune responses in oviduct epithelial cells that contribute to the fibrosis and scarring that lead to reproductive sequelae in clinical disease.…”
Section: Discussionsupporting
confidence: 65%
“…In our previous investigations into the role of TLR3 in the pathogenesis of genital infections in mice, one key aspect of TLR3 deficiency that we observed was that mice deficient in TLR3 appeared exhibit indicators of more pronounced chronic sequelae, such as lymphocytic endometritis and hydrosalpinx (32). To examine whether TLR3 has a similar role in the pathogenesis of genital tract Chlamydia infections in humans, we next measured the Chlamydia -induced synthesis of biomarkers associated with chronic inflammatory disease and tissue necrosis in the WT and TLR3 deficient hOE cells.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Toll‐like receptor 4 (TLR4), a lipopolysaccharide receptor, might trigger the activation of the extracellular signaling pathway. Disorder of TLR4 contributed to the process of excessive release of inflammatory cytokines (Carrasco et al, ). In the network, there were two targets interacting with TLR4, which suggested that it is an important pathway for the treatment of PID.…”
Section: Resultsmentioning
confidence: 99%